Manajemen Perubahan Kurikulum Dari K-13 ke Kurikulum Merdeka di Madrasah Ibtidaiyah Swasta Al-Hikmah Kecamatan Beringin Deli Serdang - Neliwati; Rabbirham; Siti Aisyah; Raudatun Annisa (EduInovasi: Journal of Basic Educational Studies, 2024)
The purpose of this research is to determine the curriculum change management from the 2013 Curriculum to the Merdeka Curriculum at the Private Madrasah Ibtidaiyah Al-Hikmah, Beringin District, Deli Serdang. The research method used is qualitative with a case study approach. The results showed that the curriculum change management process at the Private Madrasah Ibtidaiyah Al-Hikmah includes planning, organizing, implementing, and evaluating. The conclusion of this research is that the curriculum change management from the 2013 Curriculum to the Merdeka Curriculum at the Private Madrasah Ibtidaiyah Al-Hikmah, Beringin District, Deli Serdang has been implemented well.